PENGARUH PERTUMBUHAN PERUSAHAAN, STRUKTUR MODAL, KINERJA KEUANGAN DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN - Kaltsum, Ummi; Afandi, Agus (Publika Citra Media, 2025)
This research aims to examine the influence of company growth, capital structure, financial performance and good corporate governance on company value in primary consumer goods sector companies listed on the Indonesia Stock Exchange in 2018- 2022. This research uses quantitative research and the data used in this research is secondary data in the form of annual reports for the 2018-2022 period. The number of samples used in this research was 135 from 27 companies in the population of companies in the primary consumer goods sector. By using a purposive sampling method based on predetermined criteria. Based on research that has been conducted, it shows that company growth, capital structure, financial performance and good corporate governance simultaneously influence company value. Company growth, capital structure and good corporate governance have no effect on company value. Meanwhile, financial performance influences company value.